2007
DOI: 10.1897/06-581r.1
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and bioanalysis of the ecotoxicologically relevant fraction of contaminants in sediments

Abstract: Assessments of the risk connected to the contamination of soils and sediments should rely on a multidisciplinary approach based on both chemical and biological techniques (i.e., the sum of exposure and effects assessment). The dioxin-responsive, chemical-activated luciferase expression (DR-CALUX) bioassay is widely applied for evaluation of the toxicity of sediments after an exhaustive extraction of the contaminants, and results are used for risk assessment purposes. Approaches based on total extraction of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Fractions 13-17 (generally polar contaminants) were toxic for both dosing methods, whereas fractions containing PAHs were only toxic for the DMSO dosing. This is in accordance with the idea that solvent extraction of sediment samples may overestimate the bioavailability and thus the hazard of hydrophobic toxicants (29). Fractions 2-5 of two of the three sediment extracts only showed effects when dosed with SR.…”
Section: Resultssupporting
confidence: 90%
“…Fractions 13-17 (generally polar contaminants) were toxic for both dosing methods, whereas fractions containing PAHs were only toxic for the DMSO dosing. This is in accordance with the idea that solvent extraction of sediment samples may overestimate the bioavailability and thus the hazard of hydrophobic toxicants (29). Fractions 2-5 of two of the three sediment extracts only showed effects when dosed with SR.…”
Section: Resultssupporting
confidence: 90%
“…Good correlations between bioavailability and the rapid-desorbing fraction were found in previous studies, in which organisms such as earthworms, Oligochaetes and microbe were investigated [2,[10][11][12][13]. Therefore, the rapid-desorbing fraction was regarded as a good predictor for the bioavailability of POPs in soil [5,6,8,10,12,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 73%
“…However, it takes a long time for the consecutive desorption to predict the rapid-desorbing fraction, thus efforts have been made to overcome this shortcoming, and the single-point extraction (the Tenax beads were added only once and removed after extraction for several hours, e.g., 6 h) has been developed [5,10,18,[27][28][29]. Cornelissen et al [5] found Tenax 6 h-extracted fraction was about 0.5 times the rapid-desorbing fraction, later, more evidences also validated that both rapid-desorbing fraction and single-point extracted fraction were good predictors for the bioavailability of organic pollutants in sediment or soil [8,10,12,[14][15][16]18,19]. In recent years, Tenax extraction was widely applied to assess the bioavailability of POPs in soil even though it had not been standardized by such international organizations as International Standardization Organization (ISO) [2,11,18,27,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure involves adding HPCD solution into a soil or sediment sample, mixing for a predetermined time interval (e.g., 20 h) and then centrifugation to obtain the supernatant to be used for analysis. HPCD extraction has mainly been used to study and predict the biodegradation of PAHs (Cuypers et al, 2002; Doick et al, 2006; Reid et al, 2000; Rhodes et al, 2008, 2010; Stroud et al, 2009; van der Heijden and Jonker, 2009), organochlorines (Wong and Bidleman, 2010), PCBs (Puglisi et al, 2007; Wong and Bidleman, 2010), linear alkylbenzenes (Dew et al, 2005), and aliphatic hydrocarbons (Stroud et al, 2008, 2009) in soils or sediments. Reid et al (2000) used an excess of HPCD in aqueous solutions to extract soil-associated 14 C phenanthrene.…”
Section: Partial Extraction Methods For Measuring Bioaccessibilitymentioning
confidence: 99%